The man in the maze : science fiction - Silverberg, Robert (Sidgwick & Jackson, 1969)
A man who has encountered and communicated with an alien race is persuaded to leave his self-imposed exile in the labyrinths of an old city on a long-dead planet to help Earth fend off an invasion.